Effect of Corporate Governance on Employee’s Performance in Nepalese Commercial Banks - Magar, Saroj; Shikhrakar, Shreeshma; Poudel, Shweta; Poudel, Susant (Nepalese Journal of Economics, 2024)
This study examines the impact of corporate governance on employee performance in Nepalese insurance companies. Employee performance is the dependent variable. The independent variables are shareholder rights, transparency and disclosure, compensation, risk management, corporate social responsibility, compliance and legal framework and ethics and integrity. The primary source of data is used to assess the opinions of the respondents regarding corporate governance and level of performance in Nepalese commercial banks. The study is based on primary data which were collected from 100 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The regression models are estimated to test the significance and importance of corporate governance on employee performance in Nepalese commercial banks. The study showed that shareholder rights have positive impact on employee performance. This reveals that increase in the protection of shareholder rights leads to increase in employee performance. The study also showed that transparency and disclosure have positive impact on employee performance. It implies that increase in transparency and disclosure leads to increase in employee performance. In addition, compensation has a positive impact on employee performance. It indicates that fair compensation leads to increase in employee performance. Similarly, risk management has a positive impact on employee performance. It reveals that better the management of risk, higher would be the employee performance. The result also shows that corporate social responsibility has a positive impact on employee performance. This implies that increase in corporate social responsibility leads to increase in employee performance. Furthermore, compliance and legal framework have positive impact on employee performance. It reveals that better compliance and legal framework leads to increase in employee performance. Similarly, ethics and integrity have positive impact on employee performance. It reveals that better the ethics and integrity, higher would be the employee performance.